High‐Content Screening for Protein‐Protein Interaction Modulators Using Proximity Ligation Assay in Primary Neurons. Issue 1 (26th December 2019) - Mendes, Tiago; Herledan, Adrien; Leroux, Florence; Deprez, Benoit; Lambert, Jean‐Charles; Kilinc, Devrim
Abstract: The proximity ligation assay (PLA) allows the detection and subcellular localization of protein‐protein interactions with high specificity. We recently developed a high‐content screening model based on primary hippocampal neurons cultured in 384‐well plates and screened a library of ∼1100 compounds using a PLA between tau and bridging integrator 1, a genetic risk factor for Alzheimer's disease. We developed image‐segmentation and spot‐detection algorithms to delineate PLA signals in the axonal network, but not in cell bodies, from confocal images acquired via a high‐throughput microscope. To compare data generated from different plates and through different experiments, we developed a computational routine to optimize the image analysis parameters for each plate and devised a range of quality‐control measures to ultimately identify compounds that consistently increase or decrease our read‐out. We provide the following protocols. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Routine culture of rat postnatal hippocampal neurons in 384‐well plates Basic Protocol 2 : Compound incubation using the high‐content screening platform Support Protocol 1 : Preparation of intermediate plates for compound screening Support Protocol 2 : Preparation of intermediate plates for hit validation (dose‐response curves) Basic Protocol 3 : Proximity ligation assay in 384‐well plates Basic Protocol 4 : Image acquisition and analysis Support Protocol 3 : Optimization of analysis parameters Basic Protocol 5 : Identification of hits Basic Protocol 6 : Validation of hits based on dose‐response curves